Role of Î²âlactamase in the susceptibility of clinical isolates to Î²âlactam antibiotics (Faculty of Medicine Universitas Indonesia, 2004)
Combination of Î²âlactam antibiotic with Î²âlactamase inhibitor has been proven to overcome resistance caused by Î²âlactamase production. An evaluation to the MIC of some Î²âlactam antibiotics to Î²âlactamase producing isolates will be reported. A. anitratus, E. coli, K. pneumoniae, Proteus sp, Pseudomonas sp, S. aureus, S. epidermidis, S. pneumoniae, S. viridans, and Î²âhemolytic Streptococcus, were challenged to Ampicillin/Sulbactam (AMS), Amoxicillin/Clavulanic acid (AMC), Cefoperazone (CFP), Cefoperazone/Sulbactam (CSL), Ceftriaxone (CRO), dan Cefotaxime (CTX) using ETest techniques. Î²âlactamase production was identified using Cefinase disk. Sixtyfour percent of isolates were capable of producing Î²âlactamase. All E. coli and K. pneumoniae tested were Î²âlactamase producer, none of Proteus sp, Pseudomonas sp, and S. epidermidis tested produced Î²âlactamase. In Î²âlactamase producing group, Sulbactam was able to reduce resistance to CFP from 25% to 5%. About 20% of Î²âlactamase producing isolates which were resistant to CFP, were susceptible to CSL. Susceptibility of S.viridans to AMS, AMC, CFP, and CSL was higher than 80%, but less than 50% to CRO and CTX. S. pneumoniae was less susceptible to tested antibiotics, 50 to 60% susceptibility was shown to AMC, CFP, and CSL. S.aureus was 60 to 70% susceptible, while Î²âhaemolytic Streptococcus showed good response to the tested antibiotics. Only 30% or less of K. pneumoniae and E. coli was susceptible to AMS and AMC. A. anitratus showed good susceptibility only to AMS (78%) and CSL (89%). Sixtyfour percent of isolate studied produced Î²âlactamase. Î²âlactamase inhibitor could reduce resistance of Î²âlactamase producing organism to Î²âlactam antibiotic from 25 to 5 percent. (Med J Indones 2004; 13: 140-5)Keywords: Antibiotic Susceptibility, MIC, Î²âlactam antibiotic, Î²âlactamase inhibitor